The role of CTCF binding sites in the 3′ immunoglobulin heavy chain regulatory region - Birshtein, Barbara K. (Frontiers in Genetics, 2012)
The immunoglobulin heavy chain locus undergoes a series of DNA rearrangements and modifications to achieve the construction and expression of individual antibody heavy chain genes in B cells. These events affect variable regions, through VDJ joining and subsequent somatic hypermutation, and constant regions through class switch recombination (CSR). Levels of IgH expression are also regulated during B cell development, resulting in high levels of secreted antibodies from fully differentiated plasma cells. Regulation of these events has been attributed primarily to two cis-elements that work from long distances on their target sequences, i.e., an ∼1 kb intronic enhancer, Eμ, located between the V region segments and the most 5′ constant region gene, Cμ; and an ∼40 kb 3′ regulatory region (3′ RR) that is located downstream of the most 3′ CH gene, Cα. The 3′ RR is a candidate for an “end” of B cell-specific regulation of the Igh locus. The 3′ RR contains several B cell-specific enhancers associated with DNase I hypersensitive sites (hs1–4), which are essential for CSR and for high levels of IgH expression in plasma cells. Downstream of this enhancer-containing region is a region of high-density CTCF binding sites, which extends through hs5, 6, and 7 and further downstream. CTCF, with its enhancer-blocking activities, has been associated with all mammalian insulators and implicated in multiple chromosomal interactions. Here we address the 3′ RR CTCF-binding region as a potential insulator of the Igh locus, an independent regulatory element and a predicted modulator of the activity of 3′ RR enhancers. Using chromosome conformation capture technology, chromatin immunoprecipitation, and genetic approaches, we have found that the 3′ RR with its CTCF-binding region interacts with target sequences in the VH, Eμ, and CH regions through DNA looping as regulated by protein binding. This region impacts on B cell-specific Igh processes at different stages of B cell development.